Experimental setup for high‐resolution characterization of crystal optics for coherent X‐ray beam applications. Issue 1 (9th January 2023) - Halavanau, Aliaksei; Margraf, Rachel; Robles, River; MacArthur, James; Qu, Zhengxian; Marcus, Gabriel; Wu, Juhao; Sato, Takahiro; Zhu, Diling; Takacs, Christopher J.; Arthur, Ross; Kraynis, Olga; et al.
Abstract : The article presents the rocking curve imaging instrument at Stanford Synchrotron Radiation Lightsource beamline 10‐2, which is used to characterize diamond and silicon crystals for Bragg optics applications. Abstract : Stanford Synchrotron Radiation Lightsource serves a wide scientific community with its variety of X‐ray capabilities. Recently, a wiggler X‐ray source located at beamline 10‐2 has been employed to perform high‐resolution rocking curve imaging (RCI) of diamond and silicon crystals. X‐ray RCI is invaluable for the development of upcoming cavity‐based X‐ray sources at SLAC, including the cavity‐based X‐ray free‐electron laser and X‐ray laser oscillator. In this paper, the RCI apparatus is described and experimental results are provided to validate its design. Future improvements of the setup are also discussed.